Fracture of elastic-brittle and elastic-plastic material in cantilever cyclic bending (Fracture and Structural Integrity, 2019)
The paper analyses the fatigue tests of a specimen made of 16Mo3 steel and 6082-T6 aluminium alloy performed under bending and tensile conditions. It has been shown that in the case of bending of the 16Mo3 steel specimen, in low cycle fatigue (LCF) range, the fatigue life is increased with respect to the results obtained under tension-compression conditions. On the other hand, in the case of the aluminium specimen, the load condition practically does not affect the fatigue life. Microstructural analysis revealed almost homogeneous fatigue cracks in the 16Mo3 steel samples which are practically elastic-plastic. The analysed 6082-T6 aluminium alloy belongs to the group of materials characterized by elastic and brittle properties. In the case of pendulum bending in the obtained images, it is possible to notice the clear pits at an angle of about 45 degrees relative to the surface of the breakthrough. They penetrate the broken specimen to about 33%. In the middle of the material, the bending plane is clearly visible, where the stress is constant and equals 0 MPa.
Keywords: Tension-compression; Pendulum bending; Strain-life curves